Metal Complexes of π-Expanded Ligands (4): Synthesis and Characterizations of Copper(II) Complexes with a Schiff Base Ligand Derived from Pyrene - Dien, Luong Xuan; Truong, Nguyen Xuan; Yamashita, Ken -ichi; Sugiura, Ken- ichi (VNU Journal of Science: Natural Sciences and Technology; Vol 36 No 2, 2020)
An innovative π -expanded ligand derived from salicylaldimine ligand representing pyrene ring as a substitute for benzene ring was synthesized in 5 steps from commercially available pyrene. This unique bidentate ligand ( 1 ) was coordinated to Cu(II) metal centre for affording complex  2 , which was characterized by IR, elemental, X-ray diffraction analyses, and magnetic susceptibility. Its coordination geometry is a trans -square plane with an obvious stair-step structure which is formed by two pyrene moieties and the coordination plane (CuN2O2). In addition, the dihedral angle between the coordination plane and the pyrene ring is 34.9 o and the plane of seven carbon atoms of the long alkyl chains were arranged nearly parallel to the pyrene rings. The electronic properties of this novel complex 2 were examined via cyclic voltammetry and absorption spectroscopy to show the narrower HOMO-LUMO gap than those of the complex 4 . Moreover, the particular behavior of both complexes  2  and 4 was investigated through DFT studies.